La voix étranglée de Tess - Annie Ramel (Cahiers Victoriens et Edouardiens)
In Tess of the d’Urbervilles, the motif of the stain (or spot) has a vocal quality : the vermilion words painted on the wall « shout themselves out », something is shown in the field of the gaze in lieu of the voice. Thus Tess’s voice is hardly ever heard, her lament is never vocalized, it seems to be stuck in her throat. Instead we see the « round little hole » of her mouth when Angel rejects her, or we read innumerable « O’s » on the page when she speaks. The lacanian concepts of « voice qua object » and « gaze qua object » (which are two forms of objet petit a) can throw a light on this interconnection of gaze and voice, and thereby show the modernity of Hardy’s novel.For Slavoj Žižek has argued that the « passion for the Real » was the distinctive feature of the 20th century. In normal life, the consistency of our experience of reality depends on the exclusion of objet petit a from it. What happens in Tess’s tragic world is that the object small a has somehow got stuck in her reality, it has not been fully repressed and excluded. Tess occupies a border-line position (which is tragic, not psychotic) in which the horror of the gaze qua object and the horror of the voice qua object, that is to say the horror of the Thing, are very nearly encountered, being almost unveiled and audible. Thus Tess’s throttled voice is a threat, a silent cry that will finally be silenced when she is hanged. It is a symptom of the passion for the Real, and evidence of Hardy’s modernity.